Investigation of Beam Forming Algorithms Using Smart Antenna for Modern Wireless Communication - Mallaiah, Narayanadas; Rao , N. V. Koteswara; Ramakrishna, D. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
: In Recent wireless communications especially for mobile phones the effectiveness of the system depends on how well the signal is received, with signals coming from several service providers and radio users, the wireless channels grow crowded. Enhancing a signal's quality is important under these fictitious circumstances Additionally, the current generation of services, like 5G, will use a higher frequency range and require a broader bandwidth and more channel capacity for high-speed data transfers. One of the technologies that can improves the wireless communication system is smart antenna with respect to enhancing quality, coverage, and capacity of networks while increasing efficiency. The biggest issue in a noisy setting is getting the most signal reception in the desired direction. Therefore, Adaptive algorithms contributes a key factor in obtaining the optimum signal quality with improving efficiency. In this paper we considered uniform linear array with 15 elements and performance can be investigated using adaptive beam forming algorithms Recursive Least Square (RLS), Least Mean Square (LMS) The results of simulations are carried out by using MATLABR2023A. Our focus is to improves the system efficiency with high gain towards the desired direction without any side lobes.This can be obtained by using the N-LMS algorithm